An efficient way of intra-oral sinus lavage - Jie Han Timothy Sng; Chee Weng Yong; Jing li Lum; Kang Ming Melvin Liew (Elsevier, 2021)
In this paper, we present a modified set-up of a 20 ml syringe in the use of intra-oral sinus lavage via oroantral perforations of patients. With the addition of a smallbore Tport extension, clinicians can easily replenish the syringe with saline without repeatedly re-inserting the non-bevelled needle via the oroantral perforation during multiple rounds of sinus lavage This simple method can potentially improve the efficiency and reduce patient's discomfort during intra-oral sinus lavage.